2014
DOI: 10.1515/jbcpp-2014-0035
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of opioidergic and serotonergic systems in the analgesic activity of Cissus quadrangularis L. stem extract in mice

Abstract: The chloroform extract was found to be more potent than methanol extract in inducing analgesic effect in mice, and the analgesic activity may be mediated through opioidergic and serotonergic pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Cissus quadrangularis treatment improved metabolic parameters in rats on a high-fat diet. Studies have explored the pharmacological properties of Cissus quadrangularis , including anti-inflammatory [ 14 , 15 ] analgesic [ 15 , 16 ], antimicrobial [ 17 ], and antioxidant effects [ 18 ]. The plant’s medicinal properties are linked to bioactive compounds such as resveratrol, piceatannol, pallidol, parthenocissine A, stilbene derivatives, and quadrangularins A, B, and C [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cissus quadrangularis treatment improved metabolic parameters in rats on a high-fat diet. Studies have explored the pharmacological properties of Cissus quadrangularis , including anti-inflammatory [ 14 , 15 ] analgesic [ 15 , 16 ], antimicrobial [ 17 ], and antioxidant effects [ 18 ]. The plant’s medicinal properties are linked to bioactive compounds such as resveratrol, piceatannol, pallidol, parthenocissine A, stilbene derivatives, and quadrangularins A, B, and C [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Veldt Grape is a vining plant native to India and Africa that has been used medicinally for centuries in these regions by traditional practitioners. A lot of research has been conducted globally on the efficacy of Cissus quadrangularis including, its anti-inflammatory effects [11][12] , anti-osteoporotic effects 13 , Antioxidant activity 14 , and effects on skeletal systems 15 . Pandit et al (2020) reported the antifungal effects of Cissus quadrangularis extract on onchomycosis rather than fluconazole 16 .…”
Section: Introductionmentioning
confidence: 99%
“…In Africa, this plant is used against gout, venereal diseases, leucorrhoea, syphilis, haemorrhoids, diarrhoea, dysentery and as an aphrodisiac (Shirwaikar et al, 2003). Work carried out on C. quadrangularis has shown its analgesic (Dora et al 2017), antiin ammatory (Banu et al 2012;Nie et al 2015), anti-osteoporotic (Potu et al 2009) and antioxidant (Lekshmi et al 2015) properties, its effects on the skeletal system (Bhagat et al 2009), antibacterial, antifungal, deworming, antihemorrhoidal and analgesic (Mishra et al 2010)…”
Section: Introductionmentioning
confidence: 99%